Designing A Speaking Test for Special Purposes (SP) in Hiring Experts for a Company - Salam, Md. Abdus (Indonesian Journal of EFL and Linguistics, 2026)
Designing speaking tests for special purposes involves contentious debates regarding specific contexts, company goals, and learner requirements, and hence, requires further research. This article designs a speaking test for the specific purpose of recruiting company professionals. At present, multinational companies around the globe are evolving day by day, and their sister concerns are getting diverse perspectives. The research objective of this article is to design a speaking test. This study requires finding an answer to the research question: how to design a valid and reliable speaking test for recruiting company professionals? This study applied a qualitative data analysis approach to find an answer to the research question, in which research articles, books, periodicals, and magazines were treated as secondary, and the speaking test design was primary data. This study finds that multiple challenges are present in designing a speaking test, keeping in mind the reliability and validity of the tests, like test-time, assessment-criteria, validity, and reliability. The findings of this article will be helpful and have positive impacts for the examinees as well as the employers. Observing the necessities, this study recommends further research for designing a speaking test, keeping real-world relevance in all contexts.